Meningkatkan Pertumbuhan Rohani Jemaat Kristus Tentang Makna Persekutuan Ibadah Berdasarkan “Ibrani 10:25” - Helvin Murni Gulo; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
A growing church is a chursh that is faithful in carrying out its main task of evangelism. A growing church will always obey the commands of the lord jesus as stated in matthew 28:18-20. The goal is to spread the gospel and bring new people into the church congregation. When we talk about churches, we are no only talking about mangnificent physical buildings, but also about the individuals who believe in those churches. The true calling of the church is to be salt and light in this world. The church has the responsibility to be ambassadors who announce the news of salvation to everyone